The star formation history of the Universe as revealed by deep radio observations - Seymour, Nick; Dwelly, T.; Moss, D.; McHardy, I.; Zoghbi, A.; Rieke, G.; Page, M.; Hopkins, A.; Loaring, N. (Oxford University Press, 2008)
Discerning the exact nature of the sub-mJy radio population has been historically difficult due to the low luminosity of these sources at most wavelengths. Using deep ground based optical follow-up and observations from the Spitzer Space Telescope we are able to disentangle the radio-selected active galactic nuclei (AGN) and star-forming galaxy (SFG) populations for the first time in a deep multifrequency VLA/MERLIN Survey of the 13H XMM-Newton/Chandra Deep Field. The discrimination diagnostics include radio morphology, radio spectral index, radio/near-infrared (near-IR) and mid-IR/radio flux density ratios. We are now able to calculate the extragalactic Euclidean normalized source counts separately for AGN and SFGs. We find that while SFGs dominate at the faintest flux densities and account for the majority of the upturn in the counts, AGN still make up around one quarter of the counts at ~50 µJy (1.4 GHz). Using radio luminosity as an unobscured star formation rate (SFR) measure we are then able to examine the comoving SFR density of the Universe up to z = 3 which agrees well with measures at other wavelengths. We find a rough correlation of SFR with stellar mass for both the sample presented here and a sample of local radio-selected SFGs from the 6df-NVSS survey. This work also confirms the existence of, and provides alternative evidence for, the evolution of distribution of star formation by galaxy mass: 'downsizing'. As both these samples are SFR-selected, this result suggests that there is a maximum SFR for a given galaxy that depends linearly on its stellar mass. The low 'characteristic times' (inverse specific SFR) of the SFGs in our sample are similar to those of the 6dF-NVSS sample, implying that most of these sources are in a current phase of enhanced star formation. © 2008 RAS.